2019
DOI: 10.1002/ana.25392
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Pathological Influences of Tau Pathology in Lewy Body Disorders

Abstract: Objective: To use digital histology in a large autopsy cohort of Lewy Body Disorder (LBD) patients with dementia to test the hypotheses that co-occurring Alzheimer’s disease (AD) pathology impacts the anatomic distribution of α-synuclein (SYN) pathology and that co-occurring neocortical tau pathology in LBD associates with worse cognitive performance and occurs in a pattern differing from AD. Methods: Fifty-five autopsy-confirmed LBD (PDD: 36, DLB:19) patients and 25 AD patients were studied. LBD patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
132
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 96 publications
(159 citation statements)
references
References 54 publications
(186 reference statements)
15
132
1
Order By: Relevance
“…We also found that tau in LBD occurred in a different distribution than in AD, with more relative temporal neocortical pathology. Last, we also found that regional tau burden was consistently related to worse cognitive performance both on measures of global cognition and domain‐specific testing . Another recent digital study of LBD found relative sparing of tau pathology in the hippocampus of LBD patients with AD copathology, compared to patients with clinical AD and mixed AD and SYN pathology .…”
Section: Ad Neuropathologysupporting
confidence: 75%
See 4 more Smart Citations
“…We also found that tau in LBD occurred in a different distribution than in AD, with more relative temporal neocortical pathology. Last, we also found that regional tau burden was consistently related to worse cognitive performance both on measures of global cognition and domain‐specific testing . Another recent digital study of LBD found relative sparing of tau pathology in the hippocampus of LBD patients with AD copathology, compared to patients with clinical AD and mixed AD and SYN pathology .…”
Section: Ad Neuropathologysupporting
confidence: 75%
“…Digital histological measurements, using image analysis techniques, offer a potential improvement over traditional methods by generating objective, finely grained, continuous measurements of pathological burden, which, in contrast to the traditional methodology, may improve the potential to make clinicopathological correlations and relate pathological burden to ante mortem biomarker assessments. However, more work is needed to standardize methodology across labs . In our recent work using digital histology, we found that co‐occurring tau and Aβ pathology was related to a higher burden of neocortical SYN in patients with LBD.…”
Section: Ad Neuropathologymentioning
confidence: 99%
See 3 more Smart Citations